A Solution to the Fiat Currency Problem: Uranium and Thorium Coins - Pirot, Florent; Lavin, Claire (European Journal of Applied Sciences, 2025)
Ludwig von Mises' concept of "barter-fiction," a theoretical market in which transactions occur through direct exchange, could potentially become feasible with the introduction of uranium and thorium-based currency. These currencies, containing energy in the form of nuclear fission, could replace fiat money by being used for a wide range of practical applications, from powering cars and homes to facilitating public services. Uranium and thorium have high energy density and produce low gamma radiation, making them suitable for use as money, with the added benefit of being traceable via gamma spectrometry to prevent contamination, such as from plutonium. In these systems, the coins could act as sources of nuclear fuel, facilitating energy production via subcritical reactors that utilize both fast and slow neutrons. Proper safeguards, including plastic shielding, would be necessary to ensure safety and prevent misuse, such as the addition of harmful materials like crematory plutonium. This nuclear-based monetary system could potentially replace fiat money, which suffers from inflation and instability. The use of uranium and thorium coins would encourage responsible mining and land use, aligning monetary creation with tangible resources. Banks, potentially also mining operators, could issue these currencies responsibly, limiting supply and ensuring value creation through work, unlike fiat money, which is often inflated irresponsibly. This system would discourage the creation of harmful or inefficient materials, such as sodium-mash bombs, which would have limited military applications. In a world where the market values uranium and thorium more than fiat money, the financial landscape would shift toward more sustainable, accountable forms of currency.